A 2-Year Follow-Up After a 2-Year RCT with Vitamin D and Exercise: Effects on Falls, Injurious Falls and Physical Functioning Among Older Women. (21st March 2017) - Uusi-Rasi, Kirsti; Patil, Radhika; Karinkanta, Saija; Kannus, Pekka; Tokola, Kari; Lamberg-Allardt, Christel; Sievänen, Harri
Abstract: Background: Both exercise and vitamin D are recommended means to prevent falls among older adults, but their combined effects on fall-induced injuries are scarcely studied. Methods: A 2-year follow-up of a previous 2-year randomized controlled trial with vitamin D and exercise (Ex) of 409 older home-dwelling women using a factorial 2 × 2 design (D − Ex −, D + Ex −, D − Ex +, D + Ex + ). Besides monthly fall diaries, femoral neck bone mineral density (fn-BMD), and physical functioning were assessed at 1 and 2 years after the intervention. Results: After the intervention, S-25OHD concentrations declined to baseline levels in both supplement groups. The groups did not differ for change in fn-BMD or physical functioning, except for leg extensor muscle strength, which remained about 10% greater in the exercise groups compared with the reference group (D − Ex − ). There were no between-group differences in the rate of all falls, but medically attended injurious falls reduced in D + Ex − and D − Ex + groups compared with D − Ex − . However, all former treatment groups had less medically attended injured fallers, HRs (95% CI) being 0.62 (0.39–1.00) for D + Ex −, 0.46 (0.28–0.76) for D − Ex +, and 0.55 (0.34–0.88) for D + Ex +, compared with D − Ex − . Conclusions: Exercise-induced benefits in physical functioning partly remained 2 years after cessation of supervised training. Although there was no difference in the rate of all falls, former exercise groups continued to have lower rate of medically attended injured fallers compared with referents even 2 years after the intervention. Vitamin D without exercise was associated with less injurious falls with no difference in physical functioning.